2018
DOI: 10.1093/aje/kwy096
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of 27 Genera of Human Gut Microbiota in Ischemic Heart Disease, Type 2 Diabetes Mellitus, and Their Risk Factors: A Mendelian Randomization Study

Abstract: Manipulation of the gut microbiota presents a new opportunity to combat chronic diseases. Randomized controlled trials of probiotics suggest some associations with adiposity, lipids, and insulin resistance, but to our knowledge no trials with "hard" outcomes have been conducted. We used separate-sample Mendelian randomization to obtain estimates of the associations of 27 genera of gut microbiota with ischemic heart disease, type 2 diabetes mellitus, adiposity, lipid levels, and insulin resistance, based on sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 69 publications
9
57
0
1
Order By: Relevance
“…Observations of high abundance of Lactobacillus (3) and decreased abundance of Akkermansia in NewDMs corroborate previous findings (5). In KnownDMs, we found increased abundance of Megasphaera, Escherichia, and Acidaminococcus and decreased abundance of Sutterella, which is similar to earlier findings (6,(49)(50)(51). de la Cuesta-Zuluaga et al reported that metformin treatment in diabetics is associated with increased abundance of Megasphaera in the Colombian population (39).…”
Section: Discussionsupporting
confidence: 91%
“…Observations of high abundance of Lactobacillus (3) and decreased abundance of Akkermansia in NewDMs corroborate previous findings (5). In KnownDMs, we found increased abundance of Megasphaera, Escherichia, and Acidaminococcus and decreased abundance of Sutterella, which is similar to earlier findings (6,(49)(50)(51). de la Cuesta-Zuluaga et al reported that metformin treatment in diabetics is associated with increased abundance of Megasphaera in the Colombian population (39).…”
Section: Discussionsupporting
confidence: 91%
“…supported by both 16S rRNA and WGS data after imputation. Notably, in the magenta squares, Acidaminococcus has correlations with Dialister and Blautia only after imputation, and this result is consistent with the literature: Acidaminococcus and Dialister are both reported to have low abundances in healthy human stool samples[89]; Acidaminococcus and Blautia are both associated with risks of T2D and obesity, lipid profiles, and homeostatic model assessment of insulin resistance[90]. The green squares contain three bile-tolerant genera: Alistipes, Bilophila,…”
supporting
confidence: 81%
“…Besides the main results from nal conditional Logistic regression analyses, we also found signs of gut microbial dysbiosis indicated by signi cantly differentiated relative abundances in other taxa. For instance, SCFA producing Anaerostipes was under-represented in GDM group and has been previously found nominally associated with type 2 diabetes mellitus [26], which was elevated along with alleviation of in ammation in animal models [27,28]. On the other hand, we found several taxa including Ruminococcaceae spp., Veillonellaceae and opportunistic pathogens Enterobacteriaceae of Proteobacteria were signi cantly over-represented in GDM cases.…”
Section: Discussionsupporting
confidence: 59%